Optimalisasi Pemahaman Tugas Praktik pada Pembelajaran Jarak Jauh dengan Menggunakan Media YouTube - Mas Ning Zahroh (Neolectura, 2021)
This study aims to see the optimization of the understanding of practical tasks in distance learning using YouTube media. The method used in this research is the ex post facto method. The object of this research is Gunadarma University students who take the General Management course totaling 297 students. Based on the research conducted, it is known that giving examples of practical assignments submitted through YouTube, can provide an optimal understanding of practical assignments to as many as 272 students. These results indicate that giving examples of practical assignments through YouTube in distance learning has proven optimal for 91.6% of students. For this reason, in giving practical assignments, educators should provide examples in the form of videos that can be accessed easily by students. One of the popular video player media and easily accessible online by students is by using YouTube media.